Arbitrator's juris - Zakaria, Intan Bayani (2010)
Arbitration has been recognised as one of the alternative dispute resolutions in construction industry. By the insertion of arbitration clause in a construction contract, it requires parties to resolve any disputes through an arbitrator instead of a judge. But in some circumstances, the parties of the contract must refer their dispute to the court. Under Arbitration Act 1952, certain disputes had been barred from arbitration including fraud related disputes. The disputant parties must apply to the High Court for fraud related dispute settlement. Currently under Arbitration Act 2005 which applied UNCITRAJL Model Law, provision that takes away arbitrator’s jurisdiction to deal with question of fraud has not been brought into force. Therefore, this research has been done to explore whether in the absence of express provision relating to fraud, does it really means that the arbitrator has jurisdiction to deal with this matter. The research has been conducted by analyzing relevant cases reported in Malaysian law journals and other countries that follow the UNCITRAL Model Law which included United Kingdom, India and Hong Kong. The result shows that fraud is a question of law. Subsequently, when fraud has been established as a question of law, arbitrator has no jurisdiction to deal with it. With reference to arbitration agreements in the standard forms of contract and institutional arbitration rules, there is no express provision that gives power to arbitrator to deal with fraud. In Arbitration Act 2005, does not expressly prohibits arbitrator from dealing with question of law. Therefore, if the parties, in the arbitration agreement, agree to give such power to the arbitrator, then he would have such jurisdiction.